Pengaruh Pemberian Vitamin D Terhadap Kadar Malondialdehyde (MDA) Pada Mahasiswa Tahun Pertama Fakultas Kedokteran Universitas Pattimura - Priyosahubawa, Suluh; Angkejaya, Ony W.; de Lima, Filda V.I; Sanaky, Marliyati; Abbas, Mutmainnah; Agustin, Rachmawati D (Poltekkes Kemenkes Yogyakarta, 2025)
High levels of free radicals induce oxidative stress. In young adults, as students, the increase of free radicals is triggered by psychological stress, obesity, and lack of physical activity. Malondialdehyde (MDA) is the product of lipid peroxidation by free radicals, which can be used as a marker of oxidative stress. Free radicals can be neutralized by antioxidants such as vitamin D. This study aims to determine the effect of vitamin D supplementation on malondialdehyde (MDA) levels in first-year medical students at the Faculty of Medicine, Pattimura University. This is an experimental analytic study with a pretest-posttest control group design approach. The data used were primary data taken from 22 samples given vitamin D for 10 days and 22 control samples. Measurement of plasma MDA in this study was performed using the TBARS method. The result shows a decrease in plasma MDA levels in the intervention group with a significant p-value = 0.001. This indicates the potential of vitamin D to be used as an antioxidant. Further research is needed to determine the exact mechanisms related to this antioxidant effect..